Powering Brand Success: The Impact of Firm-Created and User-Generated Content on Equity, Attitude, and Purchase Intentions - Soekotjo, Sundari; Lestari, Setyani Dwi; Hendrawan, Koen; Brabo, Nora Andira; Iswati, Heni (Manunggal Halim Jaya, 2025)
This study aims to analyze the impact of Firm Created Content (FCC) and User Generated Content (UGC) on brand equity and purchase intention of Grab-and-Go coffee brand. In today's digital era, content generated by both companies and users plays a critical role in shaping consumer perceptions of brands. FCC refers to all content created by companies to promote their products and services, while UGC is content created by consumers that reflects their experiences with a product. This research employs a quantitative method using an online survey involving 300 respondents who are consumers of Grab-and-Go coffee. The results of the study indicate that both FCC and UGC have a significant impact on brand equity. High-quality FCC can enhance brand awareness, perceived quality, and consumer loyalty. On the other hand, positive UGC can strengthen the emotional connection between consumers and the brand, as well as increase consumer trust. Furthermore, the study also finds that strong brand equity contributes to an increase in purchase intention. Data shows that 75% of respondents are more likely to purchase Grab-and-Go coffee products after being exposed to engaging content from both the company and users. Through this analysis, the study provides valuable insights for marketers in designing effective content strategies to enhance brand equity and drive purchase intention. The findings are expected to serve as a reference for other coffee companies in leveraging FCC and UGC to achieve a competitive advantage in an increasingly competitive market. The study also recommends that companies be more proactive in encouraging consumer participation in content creation and utilize social media platforms to enhance engagement with their audience.